Pesquisas sobre o negro e a educação no Brasil: uma análise de suas concepções e propostas. - Ribeiro, Cristiane Maria (2005)
This abstract aimed at exploring the education/pedagogical proposal of researches regarding the theme of blocks and education and understanding the extent of black understanding race relations and education that underline such a proposal. For this task 101 studies were analyzed, including masters dissertations, doctoral theses, and post-doctorate studies carried out in Brazil between the seventies and the first semester of 2004. In our study we present four paradigmatic moments in studies on blacks in Brazil. The first has its historical setting at the end of the XIX century and dawn of the XX and among its postulations are found assumptions concerning black inferiority , both cultural and biological. A second interpretation of blacks in Brazilian social thought saw its greatest expression in the thirties and forties of the XX century and primarily took for granted the assumed harmonic pattern in social relations. Another interpretation of race relations evolved the studies carried out by researchers of the São Paulo School (Escola Paulista) and their followers. Among their principal arguments is the assertion that the past pratice of slavery is largely responsible for the present situation of blacks in Brazil. We also put forth the interpretation lead Hasenbalg that presupposes the deliberate relegation of questions of black Brazilians to mere questions of class. At the same time we explore studies that point out increased appreciation of the unique aspects of the situation of black Brazilian referring to concepts of ethnic identity and ethnicity. The study´s data presents a survey of research on the theme of blacks and education in Brazil various aspects, such as: profile of researchers and studies, ideas and proposals/suggestions that recommend the necessary modifications to the Brazilian educational system in order to provide an education that respects ethno-cultural diversity.